A University-Wide Preparedness Effort in the Alert Phase of COVID-19 Incorporating Community Mental Health and Task-Shifting Strategies: Experience from a Bornean Institute of Higher Learning - Mohamad Hafiz Mukhsam; Mohammad Saffree Jeffree; Nicholas Tze Ping Pang; Syed Sharizman Syed Abdul Rahim; Azizan Omar; Muhammad Syafiq Abdullah; Khamisah Awang Lukman; Nelbon Giloi; Loganathan Salvaraji; Mohd Rahimie Abd Karim; Sahipudin Saupin; Yeap Boon Tat; et al. (2020)
The COVID-19 pandemic caught the world by surprise, causing millions of confirmed cases and hundreds of thousands of deaths. Hence, the Malaysian government announced a Movement Control Order at the start of the containment phase to flatten the epidemiological curve. Universiti Malaysia Sabah (UMS), a public university in Borneo, was accelerated into alert phase because of high risk of case importation from more than 400 China incoming undergraduates. Measures to mitigate the potential COVID-19 outbreaks in its population were taken by using conventional public health measures with special attention to task-shifting and widespread community mental health interventions. A Preparedness and Response Centre was established to overseer the mitigating measures happening inside the university. Measures taken included empowerment of frontline staff, strengthening of restrictions, strengthening university health center, vigorous contact tracing, widespread health education, maintaining cultural sensitivity, and establishment of early standard operating procedures and university continuity plans. Hence, UMS was able to ensure no importation of cases into its campus during both acute and containment phases at the nationwide level.